Human intestinal spirochaetosis in Parma: a focus on a selected population during 2002-2005 - Peruzzi, S.; Gorrini, C.; Piccolo, et al., G. (Acta Biomedica Atenei Parmensis, 2007)
Background and aim of the work: Human intestinal spirochaetosis (HIS) is a large bowel infection characterised by the colonization of the intestinal mucosa by spirochaetes belonging to the genus Brachyspira. The causative agents of HIS are Brachyspira aalborgi and Brachyspira pilosicoli. Symptoms of the infection, even if not specific, are long standing diarrhoea, abdominal pain, meteorism and rectal bleeding and sometimes they can suggest the clinical suspect of inflammatory bowel diseases or rectal carcinoma. Since poor data were available on the prevalence of this infection, the aim of our study was to describe the occurrence of this infection in our area in the period 2002-2005. Methods: During a period of 4 years we analysed 297 faecal samples from 99 patients selected by potential risk factors and symptomatology suspected for HIS. The diagnosis of HIS was performed by isolation and a molecular assay based on 16S rDNA restriction fragment length polymorphism (RFLP)-polymerase chain reaction (PCR). Results: From 2002 to 2005 we detected 12 cases of intestinal spirochaetosis, 7 caused by Brachyspira aalborgi, 4 by Brachyspira pilosicoli and one by both spirochaetes, which represented the first case of a mixed infection by 2 intestinal spirochaetes in our area. Conclusions: Despite the fact that HIS seems to be a low prevalence infection in our area, in a strongly selected population we found 12 cases of this infection (12.12%). These results stimulate us to extend the research of intestinal spirochaetosis in the general population, when long standing gastrointestinal disorders and potential risk factors are present.